Post Occupancy Evaluation of The COVID – 19 Isolation Room - Aria Dewanggana; Maria Ulfa; Kusbaryanto Kusbaryanto (Universitas Aisyah Pringsewu, 2021)
The Indonesian government has declared the COVID-19 outbreak a national disaster, and so far it has not been declared over. Hospitals in making special isolation rooms for COVID-19 have requirements that must be met, this is to anticipate transmission both between patients and to officers. The purpose of the study was to evaluate the post-occupancy of the Covid-19 isolation room at the As-Suyuthiyyah Hospital in Pati. This type of research uses mixed methods research with descriptive quantitative and case studies. Data were obtained from observations of the physical condition of the room, followed by environmental tests (temperature, lighting, noise, humidity, and microbiological quality), as well as questionnaire data filled out by internal and external users with descriptive presentation. The research was carried out in stages from March to November 2021. The results showed that most of the isolation rooms had met the special isolation room standards issued by the government, and most of the internal and external users felt safe and comfortable while in or using the room Pemerintah Indonesia telah menetapkan wabah COVID – 19 sebagai bencana nasional, dan hingga saat ini belum dinyatakan berakhir. Rumah Sakit dalam membuat ruang isolasi khusus COVID – 19 terdapat persyaratan yang harus dipenuhi, hal ini untuk mengantisipasi adanya penularan baik antar pasien maupun kepada petugas. Tujuan penelitian adalah untuk melakukan evaluasi pasca huni ruang isolasi covid – 19 di Rumah Sakit As-Suyuthiyyah Pati. Jenis penelitian menggunakan penelitian mixed methods dengan kuantitatif deskriptif dan studi kasus. Data diperoleh dari observasi kondisi fisik ruangan, dilanjutkan uji lingkungan (suhu, pencahayaan, kebisingan, kelembaban, dan kualitas mikrobiologis), serta data kuesioner yang diisi oleh pengguna internal dan eksternal dengan penyajian secara deskriptif. Penelitian dilakukan bertahap selama Maret sampai November 2021. Hasil penelitian didapatkan yakni ruang isolasi tersebut sebagian besar sudah memenuhi standar ruang isolasi khusus yang dikeluarkan oleh pemerintah, dan sebagian besar pengguna internal maupun eksternal merasa aman dan nyaman selama berada atau menggunakan ruangan tersebut)